Moelecular Analysis of Rare Earth Cerium-Induced Methanol Dehydrogenase from Bradyrhizobium sp. CE-3 - Fitriyanto, Nanung Agus (2010)
A group of 15 transition metals in group III of the periodic table are called lanthanoids or rare erath elements (REEs). However scandium (Sc) and Yttrium (Y) are included in the group of REE because chemical and toxicological characteristics of these twi transition metals in group III appear to be very similiar to those of REEs. Today the possiblities of exposure to REEs are great. REEs have numerous roles in industry such as computers, plasma display, hybrid cars.